Effects of diode laser irradiation and fibroblast growth factor on periodontal healing of replanted teeth after extended extra‐oral dry time. Issue 2 (25th November 2016) - Carvalho, Erica dos Santos; Rosa, Rogério Hadid; Pereira, Flávia de Moura; Anbinder, Ana Lia; Mello, Isabel; Habitante, Sandra Marcia; Raldi, Denise Pontes
Abstract: Aim: The search for effective protocols to reduce the incidence of root resorption and allow periodontal ligament repair is still challenging, given the unpredictable outcome of late tooth replantation. The aim of this study was to assess the effects of both high‐power diode laser irradiation (DL) and basic fibroblast growth factor (FGF) on the periodontal healing of replanted teeth after extended extra‐oral dry time. Methods: Maxillary incisors of 50 male rats were extracted and assigned to three experimental and two control groups ( n = 10). DL: root surfaces treated with DL (810 nm, continuous mode, 1.0 W, 30 s), FGF: topical application of FGF gel to the root surface and in the alveolar wound, DL + FGF: DL and topical application of FGF gel, C+: no treatment after extraction and immediate replantation and C−: no treatment after extraction and replantation after 60 min. In the experimental groups, the specimens were kept dry for 60 min, the pulps were removed and the canals were filled with calcium hydroxide paste prior to tooth replantation. The animals were euthanized after 60 days. The specimens were processed for radiographic, histological and immunohistochemical analyses. Results: The radiographic analysis showed fewer resorptive areas in DL + FGF ( P < 0.05). The histological and immunohistochemical analyses showed that the DL group had lower mean values of ankylosis, replacement and inflammatory resorption when compared to C−, not differing statistically from C+. DL + FGF produced significantly more collagen fibers (type I and type III) than C−, not differing from C+ in the case of type I fibers ( P < 0.05). Conclusions: DL, with or without FGF, reduced the occurrence of external root resorption and ankylosis. Periodontal healing was favored and some fiber reinsertion occurred only when FGF was used.